55.5k views
1 vote
Solve this system using ANY method 10x-2y=43y-9=15x

1 Answer

4 votes

To answer this question we will use the substitution method.

Solving the second equation for y we get:


\begin{gathered} 3y-9=15x, \\ 3y=15x+9, \\ y=5x+3. \end{gathered}

Substituting the above result in the first equation we get:


10x-2(5x+3)=4.

Adding like terms we get:


\begin{gathered} 10x-10x-6=4, \\ -6=4. \end{gathered}

Now, from the above result, we get that the system is inconsistent, therefore it has no solutions.

Answer: No solution.

User ConditionRacer
by
5.9k points